Persepsi Kader Posyandu Terhadap Pencegahan Dan Penanganan Stunting Di Kampung Rancamanyar - Hidayat, Mohammad Fachri; Titania, Shafa; Nabila, Kaisa; Yuniyanti, Afifah Tri; Kharima, Nadya (Universitas Pahlawan Tuanku Tambusai, 2024)
Margamukti Village is one of the villages in Pangalengan District which is experiencing an increase in stunting cases. Integrated Service Post (posyandu) cadres as the frontline in providing health services in the community, especially for mothers and children, play an important role in stunting prevention efforts. However, the effectiveness of handling stunting is not only a matter of service availability, but also on the understanding and perception of posyandu cadres towards their duties and responsibilities in dealing with this problem. Therefore, this study was conducted to explore cadres' views on stunting management and the challenges they face in the field, particularly in Margamukti Village, in order to optimize their role in stunting prevention. This research used a qualitative approach through a PRA (Participatory Rural Appraisal) approach. The results showed that stunting is an important problem in Margamukti Village. Based on this problem, the perception of posyandu cadres can help the community to think more deeply so that they are able to pull all the causes of the case to its roots to find out what the consequences of the stunting problem are.